Ascending aortic aneurysm causing hoarse voice: a variant of Ortner's syndrome. (11th October 2012) - Eccles, Sinan Robert; Banks, John; Kumar, Pankaj
Abstract : A 68-year-old man with a persistent hoarse voice was found to have a left vocal cord paralysis. Clinical examination revealed signs consistent with aortic regurgitation. Subsequent investigation revealed an ascending aortic aneurysm. He underwent aortic root and ascending aorta replacement and his hoarseness improved. Ortner's syndrome refers to hoarseness due to recurrent laryngeal nerve palsy secondary to a cardiovascular abnormality. Recurrent laryngeal nerve palsy due to aneurysmal dilation of the ascending aorta is extremely rare, with aneurysms of the aortic arch being a more common cause.